METODE TERAPI ISLAM DALAM PEMBINAAN MENTAL - Alang, H.M. Sattu (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2021)
Islam is a religion of therapy. In mental development, there are several Islamic instructions including; strengthening the spiritual side of the individual by instilling faith in Allah and monotheism over Him and not associating partners with Him. Mastering the physical needs of the individual by controlling all the motivations and emotions associated with it. Also, overcome lust and excessive lust and learn important ways and habits that realize mental health. By having a healthy soul, the individual has matured, both emotionally and socially to be able to form a good personality that is always coveted by every human being. In mental development of a person there are several concepts of Islamic therapy that must be given. namely free association therapy, giving full attention and following the rules of abstention. Furthermore, the method of therapy according to Islam is seen from the way of taking, the methodology of Islamic psychotherapy is based on four methods, namely the Istimbath method, which is derived directly from the Koran, the Iqtibas method, the Istiqra'iy method, and combines the comprehensive method of Jami' bayna nufus al-zakiyyah wa -al 'uqul al-shfaiyyah. There are three stages in the process of developing human mentality in the world of Sufism and Tarekat, namely: the Takhalli stage, the Tahalli stage and the Tajalli stage.